Finite elements methods for modeling the guided waves propagation in structures with weak interfaces - Hosten, Bernard; Castaings, Michel (The Journal of the Acoustical Society of America, 2005)
This paper describes two methods using a finite element (FE) code for modeling the effects of weak interfaces on the propagation of low-order Lamb modes. The variable properties of the interfaces are modeled by either a thin layer or a uniform repartition of compression and shear springs that insure the continuity of the stresses and impose a discontinuity in the displacement field. The method is tested by comparison with measurements that were presented in a previous paper [J. Acoust. Soc. Am. 113(6) 3161–3170 (2003)]. The interface was the contact between a rough elastomer with high internal damping loaded against one surface of a glass plate. Both normal and shear stiffnesses of the interface were quantified from the attenuation of A0 and S0 Lamb waves caused by leakage of energy from the plate into the elastomer and measured at each step of a compressive loading. The FE model is made in the frequency domain, thus allowing the viscoelastic properties of the elastomer to be modeled by using complex moduli as input data. By introducing the interface stiffnesses in the code, the predicted guided waves attenuations are compared to the experimental results to validate the numerical FE methods.